Inverse Probability of Treatment Weighting Analysis of Upfront Surgery Versus Neoadjuvant Chemoradiotherapy Followed by Surgery for Pancreatic Adenocarcinoma with Arterial Abutment. Issue 39 (September 2015) - Fujii, Tsutomu; Yamada, Suguru; Murotani, Kenta; Kanda, Mitsuro; Sugimoto, Hiroyuki; Nakao, Akimasa; Kodera, Yasuhiro
Abstract : Abstract: Combined arterial resection during pancreatectomy can be a challenging treatment, and outcome would be more favorable if the tumor becomes technically removable from the artery. Neoadjuvant chemoradiotherapy (NACRT) is expected to achieve locoregional control and enable margin-negative resection. To investigate the effects of NACRT in patients with pancreatic adenocarcinoma (PDAC) which were deemed borderline resectable through preoperative imaging due to abutment of the major artery, including the superior mesenteric artery (SMA) or common hepatic artery (CHA), but were still considered to be technically removable. In the current study, comparisons were make between 71 patients who underwent upfront surgery and 21 patients who underwent NACRT followed by surgery in the strategy to preserve the artery, using unmatched and inverse probability of treatment weighting analysis (UMIN000017115). Fifty patients in the upfront surgery group and 18 in the NACRT group underwent curative resection (70% vs 86%, respectively; P  = 0.16). The results of the propensity score weighted logistic regressions indicated that the incidences of pathological lymph node metastasis and a pathological positive resection margin were significantly lower in the NACRT group (odds ratio, 0.006; P  < 0.001 and odds ratio, 0.007; P  < 0.001, respectively). Among the propensity-score matched patients, the estimated 1- and 2-year survival rates in the upfront surgery group were 66.7% and 16.0%, respectively, and those in the NACRT group were 80.0% and 65.2%, respectively. In conclusion, it was suggested that chemoradiotherapy followed by surgery provided clinical benefits in patients with PDACs in contact with the SMA or CHA.